Speech-event conceptions behind discoursepragmatic characteristics of the construction ‘do and see’ in East Asian languages - Izutsu, Katsunobu; Koguma, Takeshi (Investigationes Linguisticae, 2019)
This study addresses the semantic and functional diversities of the construction literally meaning ‘do and see’ in three East Asian languages: Japanese, Korean, and Ainu. The literal sense is dominant in Ainu, the tentative sense is predominant in Japanese, and the experiential sense as well as the tentative sense is very common in Korean. The study advances a discourse-pragmatic analysis with respect to speech-event conceptions that underlie the different senses of the construction.